Creep and normalisation: exploring a strategy of social control - Carver, Ashley (Critical criminology, 2014)
In the post 9/11 world, expansion of extraordinary powers of control through criminal justice is an important area of study. However criminological study of how these powers expand into unintended areas of criminal justice is currently underdeveloped. A few notable authors have set out complimentary templates that can provide basic tools to understanding the processes by which extraordinary laws are normalised into not so extraordinary activity. By analysing, understanding and unifying the existing literature in this area, this article seeks to amalgamate the studies of control creep and normalisation of the extraordinary into one comprehensive school of thought capable of recognising, and analysing unjustified expansion of state power. Furthermore this article will analyse the G8/G20 Meetings in Ontario, Canada to demonstrate how the processes of creep and normalisation have intentionally been used to criminalise legitimate protest.